The Effectiveness of Stress Reduction Strategies for Operating Room Nursing Staff in Tertiary Hospitals on the Prevention of Metabolic Syndrome - wang, xiaoqing (Pacific International Journal, 2023)
The increase in global life expectancy, driven by economic growth, has resulted in a progressively aging population, thereby emphasizing the imperative for comprehensive elderly care services. In China, the proportion of individuals aged 60 and above has reached 18.70%, with projections indicating a rise to 34.9% by 2050. This statistics underscores the pressing need for competent professionals in the elderly care sector. However, the current education system encounters difficulties in meeting the industry’s standards, leading to a disparity between training provisions and societal demands. In light of this, the present study aims to investigate the social adaptability of higher vocational graduates specialized in elderly care services, with a specific focus on areas encompassing independent living, cognitive abilities, interpersonal skills, vocational competence, and teamwork. The findings emphasize the necessity of tailored interventions to enhance the well-being and effectiveness of these graduates. In response, several strategies are proposed, including the cultivation of transformative mindsets, character development, local alignment with development goals, and immersive field practice. This research underscores the pivotal role of higher education institutions in producing qualified professionals equipped to address the multifaceted challenges posed by an aging society.